Teaching indigenous science curriculum to Filipino kindergarten learners - Pawilen, Greg Tabios (2017)
This is a narrative result of a study on teaching indigenous Science for kindergarten in the Philippines. The researcher observed and analyzed the learners' behavior and interaction to know the effect of teaching indigenous Science enables the learners to (1) relate personal experiences to several Science concepts and skills; (2) exhibit genuine creativity; and (3) convey observations and ideas freely and accurately by using the local language as medium of instruction. The study also observed certain characteristics of kindergarten learners from indigenous communities and several indigenous teaching methods that can enhance the teaching and learning process in kindergarten, This study strongly advocates the development and teaching of an indigenous Science curriculum as a creative approach for designing a relevant and effective Science curriculum for culturally diverse learners.
Keywords: Indigenous Science Curriculum -- Methods and Teaching